Internal factors and non-performing financing in Indonesian Islamic rural banks - Rifqi Muhammad; Ahsin Suluki; Peni Nugraheni (Cogent Business & Management, 2020)
This study aims to analyse the influence of banks' internal factors on Non-Performing Finance (NPF) at Islamic rural banks (IRBs) in Indonesia. IRBs has important factor in the economic activities in Indonesia because they provide small-mid-scale financing. The internal factors consist of the Financing to Deposit Ratio (FDR), Return on Assets (ROA), Capital Adequacy Ratio (CAR), Bank size and third-party funds (TPF). The sample in this study comprised 162 IRBs using quarter-year financial reports and examined using panel data regression. The statistical results show that ROA, CAR and bank size have a significant negative effect on NPF, while FDR and TPF have no impact on NPF in IRBs. This study may contribute to the evaluation of the financial performance of IRBs in managing their financing risk.
Keywords: G21; G32; 650; NPF; internal factors; Islamic Rural Banks; financial performance; credit risk